Advancing research on the economic value of emergency care. (29th July 2019) - Risko, Nicholas; Chandra, Amit; Burkholder, Taylor W; Wallis, Lee A; Reynolds, Teri; Calvello Hynes, Emilie J; Razzak, Junaid
Abstract : Emergency care and the emergency care system encompass an array of time-sensitive interventions to address acute illness and injury. Research has begun to clarify the enormous economic burden of acute disease, particularly in low-income and middle-income countries, but little is known about the cost-effectiveness of emergency care interventions and the performance of health financing mechanisms to protect populations against catastrophic health expenditures. We summarise existing knowledge on the economic value of emergency care in low resource settings, including interventions indicated to be highly cost-effective, linkages between emergency care financing and universal health coverage, and priority areas for future research.